Insight into crustal contamination and hydrothermal alteration of the Panjal Traps (Kashmir) from O-isotopes. Issue 11 (17th June 2022) - Shellnutt, J. Gregory; Ur Rehman, Hafiz; Manu Prasanth, M.P.
ABSTRACT: Whole rock O-isotopes of the Panjal Traps are presented in order to assess the influence of crustal contamination and hydrothermal alteration in their genesis. The basalts from the eastern Kashmir Valley and Lidder Valley have enriched δ 18 OVSMOW values (9.0‰ to 12.0‰). The basalt with the lowest δ 18 OVSMOW values (9.0‰ and 9.2‰) were likely affected by deuteric alteration but their values could be close to the original melt composition as the rocks do not show trace element (Th/NbPM ≈0.8; Nb/U ≈ 50; Th/La ≈0.1) or isotopic evidence of crustal contamination ( 87 Sr/ 86 Sri  = 0.7043 to 0.7045; εNd ( t ) = +1.1 to +1.3). The δ 18 OVSMOW (> 12‰) values and Nd isotopes (εNd ( t ) < −8.6) of the silicic Panjal Traps are consistent with derivation from continental crust. The remaining mafic rocks have enriched Sr-Nd-O isotopic values that indicate crustal (10–30%) contamination (εNd ( t ) = −1.9 to −6.1; 87 Sr/ 86 Sri  = 0.7051 to 0.7087; δ 18 O = 10.1‰ to 12.0‰) with the upper flows exhibiting further enrichment by hydrothermal alteration. The basalts from the Pir Panjal Range, western Kashmir Valley, have variable Nd isotopic values (εNd ( t ) = −6.8 to +4.3) and the lowest δ 18 OVSMOW values (6.8‰ to 7.9‰) of the study. The results demonstrate that the rocks from the Pir Panjal Range preserved not only differences in radiogenic isotopes but also the O-isotopes as well. The change in the Nd and O isotopes of the basalt from Guryal Ravine and Lidder Valley to the more depleted values of the Pir Panjal Range is likely due to a transition from a chondritic mantle source to a depleted mantle source as the continental rift evolved to a sea-floor spreading environment. Graphical Abstract: uf0001